التناص وانعكاساته الجمالية في التصميم الداخلي: اليات التناص في التصميم الداخلي والعمارة - عبد النبي, منتهى (Basrah Arts Journal, 2025)
Abstract Some designers and architects have explained that the process ofIntertextuality isLink betweenHeritage elements with a modern twist FIt is a creative process in which the designer relies on his free will to enrich his design achievements. Due to the nature of thisFor spacesFor its focus on the culture of society and its adherence to the popular heritage of Baghdad..To lead usthisTo the title of the research titled "Intertextuality and its aesthetic reflections in interior designThe research consists of four chapters: Chapter One: Addressing the research problem that crystallizedBy wondering,What are the mechanisms of intertextuality that reflect the aesthetics of interior design??The research objective included: ATo reveal the reflection of the beauty of intertextuality through the design vision of interior spaces..The importance of the current research is evident.BecauseHighlights the most important pillars of intertextuality and its aesthetic reflection in design by experts.This is what the objective boundaries of the research were represented in, while the spatial and temporal boundaries were determined.In a study of intertextuality and its aesthetic reflection in restaurants with a heritage character that employed folk heritage vocabulary in their spaces or that added creative values ​​to the vocabulary of space in Baghdad, both sides of Karkh and Rusafa, since 2023 AD.The second chapter represented the theoretical framework that specialized in studying the mechanisms of intertextuality in interior design and architecture, in addition toBeauty strategy in the intertextuality methods of the design product As for the third chapter: The research relied on the descriptive approach in analyzing the research samples (comprehensive survey method) for the entire research community according to the justifications explained by the researcher for the research analysis and its analysis. As for the fourth chapter: It included the results and conclusions that were reached from this research. The fourth chapter also included the theoretical design proposals, recommendations, and a list of sources and appendices